From Supernova to Supernova Remnant: The Three-dimensional Imprint of a Thermonuclear Explosion - Ferrand, Gilles; Röpke, Friedrich (The astrophysical journal, 2019)
Recent progress in three-dimensional modeling of supernovae (SNe) has shown the importance of asymmetries in the explosion. This calls for a reconsideration of the modeling of the subsequent phase, the supernova remnant (SNR), which has commonly relied on simplified ejecta models. In this paper, we bridge SN and SNR studies by using the output of an SN simulation as the input of an SNR simulation carried on for 500 yr. We consider the case of a thermonuclear explosion of a carbon-oxygen white dwarf star as a model for an SN Ia; specifically, we use the N100 delayed detonation model of Seitenzahl et al. In order to analyze the morphology of the SNR, we locate the three discontinuities that delineate the shell of shocked matter: the forward shock, the contact discontinuity, and the reverse shock, and we decompose their radial variations as a function of angular scale and time. Assuming a uniform ambient medium, we find that the impact of the SN on the SNR may still be visible after hundreds of years. Previous 3D simulations aiming to reproduce Tycho’s SNR, which started out from spherically symmetric initial conditions, failed to reproduce structures at the largest angular scales observed in X-rays. Our new simulations strongly suggest that the missing ingredient was the initial asymmetries from the SN itself. With this work, we establish a way of assessing the viability of SN models based on the resulting morphology of the SNR.